/
/
/
Find the inverse of the relation. 17) {(-16, 3), (5, -16), (-14, -12)}
Not my Question
Flag Content

# Question : Find the inverse of the relation. 17) {(-16, 3), (5, -16), (-14, -12)} : 2162208

MULTIPLE CHOICE. Choose the one alternative that best completes the statement or answers the question.

Find the requested composition of functions.

1) Given f(x) = 7x + 8 and g(x) = 5x - 1, find fog(x).

A) 35x + 15

B) 35x + 7

C) 35x + 39

D) 35x + 1

2) Given f(x) = -5x + 2 and g(x) = 2x + 4, find gof(x).

A) x + 8

B) x - 8

C) -10x + 22

D) -10x + 8

3) Given f(x) = (x - 10/7) and g(x) = 7x + 10, find gof(x).

A) 7x + 60

B) x - (10/7)

C) x + 20

D) x

4) Given f(x) = (3/x) and g(x) = 2x2, find gof(x).

A) (3/2x2)

B) (2x2/3)

C) (18/x2)

D) (2x2/9)

5) Given f(x) = 2x2 - 3 and g(x) = (3/x), find fog(x).

A) (3/2x2 - 3)

B) (18/x) - 3

C) 6x - (9/x)

D) (18/x2) - 3

6) Given f(x) = (6/x2) and g(x) = x - 3, find gof(x).

A) (6/(x - 3)2)

B) (6/x2 - 3)

C) (3/x2)

D) (6/x2) - 3

7) Given f(x) = x2 + 8 and g(x) = x2 - 8, find fog(x).

A) x4 + 16x2 + 56

B) x4 - 16x2 + 72

C) x4 - 16x2 + 56

D) x4 + 16x2 + 72

Find f(x) and g(x) such that h(x) = (fog)(x).

8) h(x) = (1/x2 - 5)

A) f(x) = (1/x2), g(x) = x - 5

B) f(x) = (1/x), g(x) = x2 - 5

C) f(x) = (1/x2), g(x) = - (1/5)

D) f(x) = (1/5), g(x) = x2 - 5

9) h(x) = |7x + 5|

A) f(x) = |-x|, g(x) = 7x - 5

B) f(x) = x, g(x) = 7x + 5

C) f(x) = |x|, g(x) = 7x + 5

D) f(x) = -|x|, g(x) = 7x + 5

10) h(x) = (8/x2) + 7

A) f(x) = x + 7, g(x) = (8/x2)

B) f(x) = (8/x2), g(x) = 7

C) f(x) = x, g(x) = (8/x) + 7

D) f(x) = (1/x), g(x) = (8/x) + 7

11) h(x) = (6/√(10x + 7))

A) f(x) = (6/x), g(x) = 10x + 7

B) f(x) = (6/√(x)), g(x) = 10x + 7

C) f(x) = 6, g(x) = √(10 + 7)

D) f(x) = √(10x + 7), g(x) = 6

12) h(x) = (9x + 9)7

A) f(x) = 9x7, g(x) = x + 9

B) f(x) = 9x + 9, g(x) = x7

C) f(x) = (9x)7, g(x) = 9

D) f(x) = x7, g(x) = 9x + 9

13) h(x) = √(58x2 + 92)

A) f(x) = √(58x2), g(x) = √(92)

B) f(x) = √(58x + 92), g(x) = x2

C) f(x) = √(x), g(x) = 58x2 + 92

D) f(x) = 58x2 + 92, g(x) = √(x)

14) h(x) = 6(8x + 7)2 - 9

A) f(x) = (6x - 9)2, g(x) = 8x + 7

B) f(x) = 6x2 - 9, g(x) = 8x + 7

C) f(x) = 6x2 - 9, g(x) = (8x + 7)2

D) f(x) = 8x + 7, g(x) = 6x2 - 9

15) h(x) = (x5 - 4/x5 + 2)

A) f(x) = x5, g(x) = (x - 4/x + 2)

B) f(x) = x5 + 2, g(x) = x5 - 4

C) f(x) = (x - 4/x + 2), g(x) = x5

D) f(x) = (1/x5 + 2), g(x) = x5 - 4

16) h(x) = (√(x) - 5)5

A) f(x) = x5, g(x) = √(x) - 5

B) f(x) = √(x), g(x) = (x - 5)5

C) f(x) = √(x) - 5, g(x) = x5

D) f(x) = √(x)5, g(x) = x - 5

Find the inverse of the relation.

17) {(-16, 3), (5, -16), (-14, -12)}

A) {(3, -16), (-16, 5), (-12, -14)}

B) {(-16, -16), (-16, 5), (-12, -14)}

C) {(3, -16), (-14, 5), (-12, -16)}

18) {(-5, -4), (5, 4), (-3, 6), (3, -6)}

A) {(-4, -5), (4, 5), (6, 5), (-6, 3)}

B) {(-4, -5), (4, 5), (6, -3), (-6, 3)}

C) {(-4, -5), (-5, 5), (6, -3), (-6, 3)}

19) {(6, 0), (-4, 1), (-6, 2), (-8, 3)}

A) {(1, 0), (0, -6), (6, -4), (1, 2)}

B) {(1, 0), (3, -6), (6, -6), (1, 2)}

C) {(0, 6), (1, -4), (2, -6), (3, -8)}

20) {(-8, -7), (7, 8), (-4, -3), (4, 3)}

A) {(3, -4), (-4, 7), (-7, -8), (-3, 4)}

B) {(-7, -8), (8, 7), (-3, -4), (3, 4)}

C) {(3, -4), (8, 7), (-7, 7), (-3, 4)}

## Solution 5 (1 Ratings )

Solved
Algebra 9 Months Ago 88 Views